Thermal behavior of extruded and injection‐molded poly(lactic acid)–talc engineered biocomposites: Effects of material design, thermal history, and shear stresses during melt processing. Issue 32 (26th April 2017) - Barletta, M.; Pizzi, E.; Puopolo, M.; Vesco, S.; Daneshvar‐Fatah, F.
ABSTRACT: Reinforced biocomposites were compounded by the reactive extrusion of poly(lactic acid) (PLA) and chemically modified microlamellar talcs. Talc was functionalized by the hydrolysis and condensation reaction of its surface hydroxyl groups with different kinds of organosilanes, namely, 3‐aminopropyl triethoxysilane and (3‐glycidoxypropyl)trimethoxysilane, and commercially available tri‐isocyanates, namely, Bayhydur 3100 and Desmodur 3900, which feature hydrophilic and hydrophobic behaviors, respectively. PLA–talc biocomposites were also compounded by the addition of two types of reactive biodegradable compatibilizing agents, namely, maleic anhydride and glycidyl methacrylate modified PLA. The resulting compounds were melt‐processed by injection molding to get flat substrates with different formulations. The thermal responses of the extruded compounds and injection‐molded items, specifically the first and second thermal transitions, were analyzed by differential scanning calorimetry. In particular, the influence of the different material formulations, their thermal history, and/or shear stress in single‐ or multiple‐stage heating and/or melt processing on the glass transition, crystallinity, and melting behavior of the biocomposites was investigated. The experimental findings revealed that the macroscopic thermal response of the compounds (i.e., extruded pellets) and substrates (i.e., injection‐molded flat slabs) manufactured by the melt processing of the available formulations was controlled and significantly improved by the fine‐tuning of the chemical (i.e., reaction mechanisms, chemical bonds) and physical interactions (i.e., steric hindrances, physical bonds) among the modified talc, PLA, and compatibilizing agents. These results are of great practical importance and open up broader scenarios for the industrial application of biopolymers and biocomposites, specifically in all of those consumer goods where thermal stability and the preservation of mechanical performance at moderate and high temperatures of the materials are pivotal. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45179. Abstract :